Prevalence of Multidrug‐Resistant Organisms in Patients Undergoing Free Flap Reconstruction. (12th November 2020) - Hamill, Chelsea S.; Snyder, Vusala; Sykes, Kevin J.; O'Toole, Thomas
Abstract : Objectives/Hypothesis: The purpose of this study is to evaluate the relationship between antibiotic prophylaxis and prevalence of multidrug‐resistant organisms (MDRO) in patients undergoing head and neck cancer reconstruction. Study Design: Retrospective Chart Review. Methods: Retrospective review of patients who underwent head and neck free flap reconstruction at our institution between 2009 to 2016. Results: Of the 145 patients that underwent head and neck tumor removal surgery using free tissue flaps to cover the defect and therafter received antibiotic prophylaxis, 30 (20.7%) developed postoperative surgical site (n = 17, 55.7%) or distant (n = 13, 43.4%) infections. Seven had a multidrug‐resistant infection, the most common with Methicillin‐Resistant Staphylococcus aureus (MRSA). There was no significant relationship between antibiotic spectrum or duration to the development of postoperative infections or MDRO. Pseudomonas and MRSA infections were low overall with only one multidrug‐resistant Pseudomonas infection. Conclusions: The choice of antibiotic prophylaxis should cover organisms these patients are at highest risk for including anaerobes and Gram‐negative organisms. A shorter duration of antibiotic prophylaxis should be considered given no increased risk of postoperative infection nor MDRO. Finally, one must be aware of the potential threat of multidrug‐resistant Pseudomonas and MRSA amongst this vulnerable population and identity these with culture driven treatment. Level of Evidence: 4 Laryngoscope, 131:E1881–E1887, 2021